Collaborative Governance Between the Medan City Social Service and Medan Plus Foundation for the Rehabilitation of Victims of Narcotics, Psychotropics, and Addictive Substances (NAPZA) - Nadeak, Abdillah Thoib; Sihombing, Sally Marisa (Transpublika Publisher, 2025)
The city of Medan is a drug haven in North Sumatra as evidenced by the high number of drug abuse cases. Victims of drug abuse need to receive rehabilitation. The Medan City Social Service and the Medan Plus Foundation organized rehabilitation as a form of collaborative governance. This research aims to analyze collaborative governance between the Medan City Social Service and the Medan Plus Foundation for the rehabilitation of drug abuse victims. This research uses qualitative descriptive research. The data obtained was analyzed qualitatively using the collaborative governance model according to Ansell and Gash which consists of several stages, namely: initial conditions, institutional design, facilitative leadership, and collaborative processes. The research results show that first, the initial conditions between the Medan City Social Service and the Medan Plus Foundation were supported by human resource dependency. Second, the institutional design regarding drug rehabilitation is structured from the center to the regions. Third, the facilitative leadership of the Medan City Social Service leads collaboration in handling victims. Fourth, the collaborative process in drug rehabilitation runs well between the two parties through face-to-face dialogue with a sense of trust, commitment and mutual understanding based on regulations. On the one hand, both of them must remind each other and invite each other to hold meetings in collaboration.